2021
DOI: 10.1186/s12961-020-00674-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct from the COVID-19 crisis: research and innovation sparks in Brazil

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has spread throughout more than 160 countries, infecting millions of people worldwide. To address this health emergency, countries have organized the flow of production and innovation to reduce the impact on health. This article shows the response of the Brazilian scientific community to meet the urgent needs of the public unified health system [SUS], aiming to guarantee universal access to an estimated population of 211 million. By De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 12 publications
(11 reference statements)
0
26
0
5
Order By: Relevance
“…Recent experiences and evidence seem to cast doubt on the proposed theory. For instance, Brazil is located at a similar latitude and has a tropical climate quite similar to Indonesia (used as an example of positive effects in the higher duration of direct exposure to sunlight)., where is experiencing a serious crisis of COVID-19 cases and deaths [4]. Moreover, although some of the results are statistically significant in favor of a positive effect, the most important features in clinical decisionmaking and the implementation of a treatment method are clinical significance and clinical applicability, both of which do not seem to exist in this case [5].…”
mentioning
confidence: 87%
“…Recent experiences and evidence seem to cast doubt on the proposed theory. For instance, Brazil is located at a similar latitude and has a tropical climate quite similar to Indonesia (used as an example of positive effects in the higher duration of direct exposure to sunlight)., where is experiencing a serious crisis of COVID-19 cases and deaths [4]. Moreover, although some of the results are statistically significant in favor of a positive effect, the most important features in clinical decisionmaking and the implementation of a treatment method are clinical significance and clinical applicability, both of which do not seem to exist in this case [5].…”
mentioning
confidence: 87%
“…Como exemplo dessa exposição da ciência na mídia, temos estudos que analisaram como a mobilização da comunidade científica brasileira para atender às necessidades mais urgentes da COVID-19, resultou em projetos de PD&I 19,20 . As iniciativas, que em geral não contavam com SciELO Preprints -Este documento é um preprint e sua situação atual está disponível em: https://doi.org/10.1590/SciELOPreprints.2309…”
Section: A Ciência Na Mídia Durante a Covid-19unclassified
“…Powered by TCPDF (www.tcpdf.org) financiamentos novos, tiveram efeitos práticos na mitigação dos efeitos da pandemia e alguma repercussão midiática 21,22 . É importante enfatizar que a resposta das universidades só foi possível devido a décadas de investimento na criação de um verdadeiro patrimônio nacional, representado pelas universidades públicas e institutos de pesquisa como a Fiocruz e o Butantã, com equipes compostas por funcionários públicos qualificados 19 . Mesmo com verbas para pesquisa em franco declínio após 2015, a capacidade instalada foi posta em marcha, numa velocidade surpreendente, registrando-se quase 800 projetos de PD&I até 15 de maio de 2020.…”
Section: A Ciência Na Mídia Durante a Covid-19unclassified
See 1 more Smart Citation
“…The interaction of universities, industries and governments is essential. In the absence of this linkage in Brazil, it is virtually impossible to perform translational research, that is, to take the results from the bench to the bedside, and from there to the healthcare system (Rosa, da Silva, Pacheco, C. et al, 2021 In Brazil, fewer than a quarter of all students dedicated three hours or more a day to school activities in September, a study by several nongovernmental organizations showed. Almost 5 percent of students in primary school and more than 10 percent of high school students reported in January that they had dropped out of school (Human Rights Watch, 2021).…”
Section: Problemsmentioning
confidence: 99%